Left–Right Intensity Asymmetries Vary Depending on Scanner Model for FLAIR and T1 Weighted MRI Images. Issue 3 (8th February 2022) - Arani, Arvin; Schwarz, Christopher G.; Wiste, Heather J.; Weigand, Stephen D.; Cogswell, Petrice M.; Murphy, Matthew C.; Trzasko, Joshua D.; Gunter, Jeffrey L.; Senjem, Matthew L.; McGee, Kiaran P.; Shu, Yunhong; Bernstein, Matt A.; et al.
Abstract : Background: Localized regions of left–right image intensity asymmetry (LRIA) were incidentally observed on T2 ‐weighted (T2 ‐w) and T1 ‐weighted (T1 ‐w) diagnostic magnetic resonance imaging (MRI) images. Suspicion of herpes encephalitis resulted in unnecessary follow‐up imaging. A nonbiological imaging artifact that can lead to diagnostic uncertainty was identified. Purpose: To investigate whether systematic LRIA exist for a range of scanner models and to determine if LRIA can introduce diagnostic uncertainty. Study Type: A retrospective study using the Alzheimer's Disease Neuroimaging Initiative (ADNI) data base. Subjects: One thousand seven hundred fifty‐three (median age: 72, males/females: 878/875) unique participants with longitudinal data were included. Field Strength: 3T. Sequences: T1 ‐w three‐dimensional inversion‐recovery spoiled gradient‐echo (IR‐SPGR) or magnetization‐prepared rapid gradient‐echo (MP‐RAGE) and T2 ‐w fluid‐attenuated inversion recovery (FLAIR) long tau fast spin echo inversion recovery (LT‐FSE‐IR). Only General Electric, Philips, and Siemens' product sequences were used. Assessment: LRIA was calculated as the left–right percent difference with respect to the mean intensity from automated anatomical atlas segmented regions. Three neuroradiologists with 37 (**), 32 (**), and 3 (**) years of experience rated the clinical impact of 30 T2 ‐w three‐dimensional FLAIR exams with LRIA to determine the diagnostic uncertainty. Statistical comparisons between retrospective intensity normalized T1 m and original T1 ‐w images were made. Statistical Tests: For each image type, a linear mixed effects model was fit using LRIA scores from all scanners, regions, and participants as the outcome and age and sex as predictors. Statistical significance was defined as having a P ‐value <0.05. Results: LRIA scores were significantly different from zero on most scanners. All clinicians were uncertain or recommended definite diagnostic follow‐up in 62.5% of cases with LRIA >10%. Individuals with acute brain pathology or focal neurologic deficits are not enrolled in ADNI; therefore, focal signal abnormalities were considered false positives. Data Conclusion: LRIA is system specific, systematic, creates diagnostic uncertainty, and impacts IR‐SPGR, MP‐RAGE, and LT‐FSE‐IR product sequences. Level of Evidence: 2 Technical Efficacy Stage: 3